ORGANIZATION OF A SPORTS AND HEALTH ENVIRONMENT OF A HIGHER EDUCATIONAL INSTITUTION FOR STUDENTS OF A SPECIAL MEDICAL DEPARTMENT - Radaeva S.V. ,; Sosunovsky V.S. ,; Sharafeeva A.B. ,; Zhang Yaqun, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop the content of a sports and recreation project for students of a special medical group (SMG) and exercise therapy, including students with disabilities. Results and conclusions. A sports and health project "From Accessible Sports to a Healthy Mind" has been developed. The main goal of the project is to ensure accessibility in the physical activity of students with deviations in the state of health. The project provides for the peculiarities of the health status of students, the types of activities that are presented in it are available for various groups of the population, including people with disabilities. At the same time, these types of activities are of a developing nature and have a competitive form, which increases the motivation to perform movements. The results obtained from the implementation of the developed project will allow developing an innovative vector for the formation of a new concept of physical education for students of the SHG and exercise therapy, which is based on the principle of individualization of education, taking into account the conjugation of the development of bodily, motor, intellectual and professional abilities of students.